Pengaruh Profitabilitas, Growth, Leverage, terhadap Earning Response Coefficient Studi pada Perusahaan Property & Real Estate yang Terdaftar di BEI Tahun 2017-2019 - Cantyawati, Lia; Dewi, Gst. Ayu Ketut Rencana Sari (Universitas Pendidikan Ganesha, 2021)
The research aims to make a Profitability analysis, make a growth analysis, and make a leverage analysis, on the magnitude of the Earning Response Coefficient (ERC) value (The study was conducted at Property & Real Estate business companies listed on the IDX with 2017 timeframe. -2019). Earning Response Coefficient is a type of dependent variable that can be useful in research. However, the independent variables in this study are profitability, growth variables, and leverage variables. In all property business companies & Real Estate business enterprises, a collection of data forms a population in the study which has a value of 65 companies that are included in the list with a three-year timeframe on the IDX. Purposive sampling is a procedure for obtaining a research sample with a total of 42 research sample companies. This study found that profitability and growth did not have an influence on the magnitude of the ERC value. Meanwhile, leverage has an influence on the amount of ERC value.